Preparation method and application of adhesive for low-temperature curing high-bonding-strength environment-friendly plywood

By mixing polyols and polycarboxylic acids with polymer monomers, low-temperature curing environmentally friendly adhesives are prepared, which solves the problems of low release and adhesion strength of harmful chemical substances in the existing plywood industry, and achieves high adhesion strength and environmental protection. Plywood preparation, suitable for multi-field applications.

CN119119926AActive Publication Date: 2024-12-13INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411614745.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-13
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The 'trialdehyde glue' used in the existing plywood industry will release harmful chemicals such as formaldehyde during production and use, resulting in health hazards. The adhesion strength of polyvinyl alcohol-based adhesives is low, high cost, and difficult to meet environmentally friendly high adhesion needs.

Method used

Polyols and polycarboxylic acids are heat treated and mixed with polymer monomers and catalysts to prepare low-temperature curing and high bonding strength environmentally friendly adhesives for preparing plywood. The resulting plywood has high adhesion strength and is friendly to humans.

Benefits of technology

It realizes easy to obtain raw materials, mild reaction conditions and simple process. The prepared adhesive has high bonding strength, low glass transition temperature and low curing temperature. It is suitable for applications in many fields and is harmless to animals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119926A_ABST
    Figure CN119119926A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an adhesive for low-temperature curing high-bonding-strength environment-friendly plywood, and belongs to the technical field of adhesive materials and polymers. The preparation method comprises the following steps: firstly, mixing polyhydric alcohol and polybasic carboxylic acid, heating, mixing with a small molecular monomer, and copolymerizing to obtain the adhesive. The preparation process is simple, the prepared adhesive has the characteristics of no toxicity, low glass transition temperature and the like, when the adhesive is applied to adhesion of plates, the adhesion strength of the plates is high, and the adhesive can be practically applied to preparation of plywood; the adhesive is applied to an animal body, does not cause structural change of skin, and is harmless to the animal body. The preparation method provided by the invention has the advantages of easily available raw materials, mild reaction conditions and the like, can be used for industrial large-scale production, and has good practicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive materials and polymers, and specifically relates to a preparation method and application of a low-temperature curing, high-bonding-strength, and environmentally friendly adhesive for plywood. Background Art

[0002] With the development of society, people's requirements for daily life are also increasing, so the demand for wooden furniture is gradually increasing. In order to meet people's demand for different home furnishing materials, the plywood industry has gradually developed. Plywood is a plate-like material prepared by gluing veneers with adhesives. Among them, adhesives are an important component of plywood and one of the important factors affecting the quality of artificial boards.

[0003] The adhesives currently used are mainly urea-formaldehyde resin, phenol-formaldehyde resin, and melamine-formaldehyde resin, collectively known as "trialdehyde glue". Among them, urea-formaldehyde resin has attracted people's attention due to its low cost, fast curing and high adhesion strength. However, "trialdehyde glue" will release harmful chemicals, such as formaldehyde, during the production and use process, which will cause harm to people's health, which greatly restricts the development of the plywood industry.

[0004] To this end, researchers have proposed the use of polyvinyl alcohol-based adhesives and isocyanate-based adhesives to achieve the preparation of plywood. Among them, the use of polyvinyl alcohol makes it difficult for the adhesive functional group to penetrate into the interior of the wood veneer and form an effective adhesive connection. The use of isocyanate increases the preparation cost of the adhesive and the adhesion strength of the plywood is low. Therefore, it is of great significance to develop environmentally friendly adhesives with high adhesion strength. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a low-temperature curing high-bonding-strength environmentally friendly adhesive for plywood, which has the advantages of readily available raw materials, environmental protection, mild reaction conditions, and simple process.

[0006] Another object of the present invention is to provide an application of a low-temperature curing, high-bonding-strength, environmentally friendly adhesive for plywood, wherein the adhesive is used to prepare plywood, and the prepared plywood has the characteristics of high adhesion strength.

[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a low-temperature curing high-bonding strength environmentally friendly adhesive for plywood comprises the following steps: firstly mixing polyol and polycarboxylic acid with water, and obtaining a colloid after heat treatment; then mixing the obtained colloid with a polymer monomer and water in proportion, and adding a catalyst to obtain a low-temperature curing high-bonding strength environmentally friendly adhesive for plywood.

[0009] Furthermore, the polyol is selected from one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, lignin sulfonate and glycerol.

[0010] Furthermore, the polycarboxylic acid is selected from one of citric acid, tartaric acid and malic acid.

[0011] Furthermore, the molar ratio of the polyol to the polycarboxylic acid is 1:1 to 1:50.

[0012] Furthermore, the temperature of the heat treatment is 80 to 120 o C, time is 8~48 h.

[0013] Furthermore, the polymer monomer is selected from one of acrylic acid, acrylamide and polyethylene glycol diacrylate; the average molecular weight of the polyethylene glycol diacrylate is 400; and the catalyst is selected from one of ammonium persulfate, sodium persulfate and potassium persulfate.

[0014] Furthermore, the mass ratio of the colloid, the polymer monomer and water is 1:1-20:1-10.

[0015] Furthermore, a method for preparing a low-temperature curing high-bonding-strength environmentally friendly adhesive for plywood comprises the following steps:

[0016] 1) Mix polyol and polycarboxylic acid in a molar ratio of 1:1~1:50, stir, and heat to 80~120 o C, react for 8-48 h to obtain a mixed colloid;

[0017] 2) The mixed colloid obtained in step 1) is mixed with the polymer monomer and water in a mass ratio of 1:1-20:1-10, a catalyst is added, and the mixture is stirred to obtain an adhesive having high adhesion strength and being harmless to the human body.

[0018] Furthermore, the low-temperature curing, high-bonding-strength, and environmentally friendly adhesive for plywood prepared by any of the above methods.

[0019] Furthermore, the adhesive is used in plywood by applying the adhesive to a veneer and obtaining the plywood after heat curing; the curing temperature is 40-90°C and the curing time is 4-48h.

[0020] Compared with the prior art, the advantages of the present invention are as follows:

[0021] 1) The raw materials used in the reaction of the present invention are widely available and environmentally friendly, the reaction conditions are mild, the preparation process is simple, and it is conducive to industrial large-scale production.

[0022] 2) The adhesive prepared by the present invention has high bonding strength, low glass transition temperature, low curing temperature and is animal-friendly, and can be applied to more fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the infrared spectrum of the adhesive;

[0024] Figure 2 It is the adhesion strength of plywood prepared with adhesive. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0026] Example 1

[0027] 0.97 g α-cyclodextrin and 1.92 g citric acid were mixed in 0.5 g water and heated at 80 o C for 24 h to obtain a colloid; the obtained colloid was mixed with 14.5 g of acrylic acid and 5 g of water, and then 0.2 g of ammonium persulfate was added to obtain a clear and transparent solution. The above solution was brushed on a wooden board at 80 o C for 12 h, plywood with high adhesion strength can be obtained.

[0028] Example 2

[0029] 1.13 g β-cyclodextrin and 1.5 g tartaric acid were mixed in 0.3 g water and heated at 90 o C for 16 h to obtain a colloid, the colloid, 27 g of acrylic acid and 10 g of water were mixed and stirred, and then 0.4 g of sodium persulfate was added to obtain a clear and transparent solution. The solution was brushed on a wooden board at 60 o C for 24 hours, plywood with high adhesion strength can be obtained.

[0030] Example 3

[0031] 1.30 g of γ-cyclodextrin and 1.34 g of malic acid were mixed in 0.4 g of water and heated at 100 °C. o C for 8 h to obtain a colloid, the colloid, 15.5 g acrylamide and 4 g water were mixed and stirred, and then 0.3 g potassium persulfate was added to obtain a clear and transparent solution. The solution was brushed on a wooden board at 90 o C for 6 h, plywood with high adhesion strength can be obtained.

[0032] Example 4

[0033] 1.30 g of γ-cyclodextrin and 0.75 g of malic acid were mixed in 0.2 g of water and heated at 80o C for 24 h to obtain a colloid, the colloid, 20 g acrylamide and 4 g water were mixed and stirred, and then 0.3 g potassium persulfate was added to obtain a clear and transparent solution. The solution was brushed on a wooden board at 60 o C for 12 h, plywood with high adhesion strength can be obtained.

[0034] Example 5

[0035] 0.97 g α-cyclodextrin and 0.95 g citric acid were mixed in 0.9 g water and heated at 80 o C for 16 h to obtain a colloid, the colloid, 18.3 g of polyethylene glycol diacrylate and 3.5 g of water were mixed and stirred, and then 0.3 g of sodium persulfate was added to obtain a clear and transparent solution. The solution was brushed on a wooden board at 80 o C for 12 h, plywood with high adhesion strength can be obtained.

[0036] Example 6

[0037] 1.13 g β-cyclodextrin and 1.20 g citric acid were mixed in 0.4 g water and heated at 80 o C for 20 h to obtain a colloid, the colloid, 15.5 g acrylamide and 4 g water were mixed and stirred, and then 0.3 g potassium persulfate was added to obtain a clear and transparent solution. The solution was brushed on a wooden board at 60 o C for 6 h, plywood with high adhesion strength can be obtained.

[0038] Example 7

[0039] 2.60 g lignin sulfonate and 2.78 g malic acid were mixed in 1.0 g water and heated at 90 o C for 24 h to obtain a colloid, and the colloid, 25.5 g of acrylic acid and 10 g of water were mixed and stirred, and then 0.8 g of potassium persulfate was added to obtain a clear and transparent solution. The solution was brushed on a wooden board at 80 o C for 12 h, plywood with high adhesion strength can be obtained.

[0040] Example 8

[0041] 1.13 g β-cyclodextrin and 1.50 g tartaric acid were mixed in 0.1 g water and heated at 100 °C. o C for 10 h to obtain a colloid, and the above colloid, 30.5 g of acrylic acid and 4 g of water were mixed and stirred, and then 1 g of ammonium persulfate was added to obtain a clear and transparent solution. The above solution was brushed on a wooden board at 80 o C for 24 h, plywood with high adhesion strength can be obtained.

[0042] Example 9

[0043] 1.94 g α-cyclodextrin and 1.92 g malic acid were mixed in 0.3 g water and heated at 100 °C. o C for 8 h to obtain a colloid, the colloid, 36.5 g acrylamide and 8 g water were mixed and stirred, and then 1.2 g sodium persulfate was added to obtain a clear and transparent solution. The solution was brushed on a wooden board at 60 o C for 15 h, plywood with high adhesion strength can be obtained.

[0044] Example 10

[0045] 1.30 g glycerol and 3.84 g citric acid were mixed in 0.8 g water and heated at 80 o C for 36 h to obtain a colloid, and the above colloid, 55.5 g acrylamide and 10 g water were mixed and stirred, and then 1.5 g potassium persulfate was added to obtain a clear and transparent solution. The above solution was brushed on a wooden board at 90 o C for 15 h, plywood with high adhesion strength can be obtained.

[0046] Comparative Example 1

[0047] Phenol (37.6 g) and formaldehyde (24.2 g) were mixed in a molar ratio of 1:2.2 to prepare phenolic resin. First, phenol, one-third of formaldehyde, and NaOH solution were mixed in a flask. The mixed solution was heated at 95 o C for 60 min. Then, the remaining formaldehyde and NaOH solution were stirred at 95 o C for 30 min, and then cool to 40 o C to obtain phenolic resin. Three-layer plywood with a size of 400×400×4.5 mm was prepared using poplar veneer as raw material. Phenolic resin was applied on both sides of the middle veneer. The plywood sample was heated at 120 o C. Hot press at 1.0 MPa for 5 min, and then perform adhesion strength test after cooling.

[0048] Embodiment 11

[0049] Take the adhesives in Examples 1-10 and Comparative Example 1 respectively, use poplar veneer as raw material, and prepare three-layer plywood with a size of 400×400×4.5 mm, and then heat cure under certain conditions to obtain plywood. Place both ends of the plywood on an Instron 5944 stretching machine for stretching, and record the obtained adhesion strength. The adhesion strength results obtained in different embodiments and comparative examples are shown in Table 1 below. It can be seen from Table 1 that the adhesive prepared by the present invention exhibits high adhesion strength and has practical application prospects.

[0050] Table 1 Comparison of the adhesion strength results of the adhesives prepared in Examples 1 to 10

[0051]

[0052] Take any of the adhesives prepared in Examples 1-10 and place it on a Nicolet iS10 Fourier transform infrared spectrometer from Bruker, Germany, and measure the infrared spectrum at 4000-400 cm in total reflection mode. -1 The infrared spectrum within the range is as follows Figure 1 As shown ( Figure 1 is the test result of Example 8), Figure 1 The infrared spectrum shows that the prepared adhesive has a large number of free hydroxyl groups and carboxyl groups, which can produce strong hydrogen bonding, thereby improving the adhesion strength. At the same time, plywood was prepared according to the method mentioned in the above embodiment, and the adhesion strength of the plywood was tested; Figure 2 is the adhesion curve of Example 8, from Figure 2 In the figure, we can see the adhesion strength of this embodiment, which is as high as 1.75 MPa.

[0053] Example 12

[0054] The adhesives obtained in Examples 1-10 and Comparative Example 1 were placed in DSC to test their o The glass transition temperature is obtained by measuring the heat change of C. The glass transition temperature results of the adhesives in Examples 1-10 and Comparative Example 1 are shown in Table 2. The results show that the adhesive has a lower glass transition temperature and a lower curing temperature.

[0055] Table 2 Comparison of glass transition temperatures of adhesives prepared in Examples 1-10

[0056]

[0057] Example 13

[0058] After thermal curing, the adhesive prepared in Example 9 was adhered to the mouse epidermis and compared with the blank mouse epidermis. The experimental results are shown in Table 3 below;

[0059] Table 3 Comparison of mouse epidermis bonded with the adhesive prepared in Example 9 and blank mouse epidermis

[0060]

[0061] Histological analysis showed that the adhesive did not cause structural changes in the skin. There was no significant difference in the thickness of the dermis and epidermis between the control sample group and the example group. Therefore, the adhesive is environmentally friendly and harmless to animals.

[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a low-temperature curing, high-bonding-strength, environmentally friendly adhesive for plywood, characterized in that: Firstly, polyol and polycarboxylic acid are mixed with water, and then a colloid is obtained after heat treatment; then the obtained colloid is mixed with polymer monomer and water in proportion, and a catalyst is added to obtain a low-temperature curing, high-bonding-strength, and environmentally friendly adhesive for plywood; the polyol is selected from one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, lignin sulfonate and propylene glycol; and the polycarboxylic acid is selected from one of citric acid, tartaric acid and malic acid.

2. The method for preparing the low-temperature curing high-bonding-strength environmentally friendly adhesive for plywood according to claim 1, characterized in that: The molar ratio of the polyol to the polycarboxylic acid is 1:1-1:

50.

3. The method for preparing the low-temperature curing high-bonding-strength environmentally friendly adhesive for plywood according to claim 1, characterized in that: The heat treatment temperature is 80~120 o C, time is 8~48 h.

4. The method for preparing the low-temperature curing high-bonding-strength environmentally friendly adhesive for plywood according to claim 1, characterized in that: The polymer monomer is selected from one of acrylic acid, acrylamide and polyethylene glycol diacrylate; the average molecular weight of the polyethylene glycol diacrylate is 400; and the catalyst is selected from one of ammonium persulfate, sodium persulfate and potassium persulfate.

5. The method for preparing the low-temperature curing high-bonding-strength environmentally friendly adhesive for plywood according to claim 1, characterized in that: The mass ratio of the colloid, the polymer monomer and water is 1:1-20:1-10.

6. The method for preparing the low-temperature curing high-bonding-strength environmentally friendly adhesive for plywood according to any one of claims 1 to 5, characterized in that: Here are the steps: 1) Mix polyol and polycarboxylic acid in a molar ratio of 1:1~1:50, stir, and heat to 80~120 o C, react for 8-48h to obtain a mixed colloid; 2) The mixed colloid obtained in step 1) is mixed with the polymer monomer and water in a mass ratio of 1:1-20:1-10, a catalyst is added, and the mixture is stirred to obtain an adhesive having high adhesion strength and being harmless to the human body.

7. An environmentally friendly adhesive for plywood which is cured at low temperature and has high bonding strength and is prepared according to the method of any one of claims 1 to 6.

8. The use of the adhesive in plywood according to claim 7, characterized in that: The method comprises the following steps: applying the adhesive to a veneer, and obtaining a plywood after heat curing; the curing temperature is 40-90° C., and the curing time is 4-48 hours.

Citation Information

Patent Citations

  • Ultrahigh solid content citric acid-based environmentally-friendly adhesive for plywood, preparation method and applications thereof

    CN110684484A

  • Polymerizable haplotype eutectic solvent, adhesive obtained by polymerization of polymerizable haplotype eutectic solvent and preparation method of polymerizable haplotype eutectic solvent

    CN116285454A

  • Environment-friendly adhesive for organic acid-polyol-based formaldehyde-free high-performance plywood as well as preparation method and application of environment-friendly adhesive

    CN116355560A

  • Preparation method of polyol carboxylic ester, polymerizable composition and adhesive

    CN117142991A

  • Preparation method of full-hydrophobic polymer adhesive based on hydrophobic deep-eutectic solvent

    CN118085770A